Pengaruh media sosial dalam penyampaian informasi terhadap minat berkunjung Kembali di Museum H. M. soeharto - Arifah, Annisa Nur; Amelia, Viona; Nugroho, Dwi Yoso (PANUNTUN (Jurnal Budaya, Pariwisata, dan Ekonomi Kreatif), 2024)
This study aims to determine how much influence social media as a forum for communication and information delivery has on the interest in revisiting HM Soeharto Museum in Yogyakarta. Through a quantitative approach, this study uses a survey method to collect data from randomly selected museum visitors. The population in this study were visitors to HM Soeharto Museum, while the sample was determined on tourists who had visited the museum before and were at least 14 years old. The data collection tool used was a closed questionnaire with a range of 1-5 Likert Scale scores. The results of data analysis showed a significant influence between the use of social media and interest in revisiting HM Soeharto Museum. The regression coefficient and correlation coefficient showed that any increase in social media usage was associated with a significant increase in interest in revisiting the museum. These findings have important implications in the context of museum promotion and marketing as well as cultural tourism activities. Visitors to HM Soeharto Museum are advised to follow their social media accounts to get the latest information. By making good use of social media, visitors can provide feedback to the museum about the experience of visiting. Visitors can also invite friends or relatives to visit together. This can contribute to increasing interest in visiting HM Soeharto Museum again and enriching visitors' experience in exploring Indonesia's historical heritage.